Role of social partners in addressing the global economic crisis - Demetriades, Stavroula; Welz, Christian (Dublin, 2012)
"This working paper examines how social dialogue has addressed the impact of the crisis. In order to make reasonable comparisons between countries as diverse as Brazil, China, Japan and the USA it is necessary to take into account the institutional, political, economic and social backgrounds. However, the purpose of this short paper was not to provide a profile of the countries included but rather to identify practices employed by the social partners in dealing with some of the great challenges caused by the crisis."